The Impact of Covid-19 pandemic on work organization - Savic, Andrijana; Dobrijević, Gordana (The European Journal of Applied Economics, 2022)
In today’s fast-moving environment, business organizations are faced with the need for frequent changes in order to overcome everyday challenges and improve their performance. Organization of work is one of the key elements in the adjustment to market changes, and the basis of enterprise transformation. Apart from continuous market competition, the COVID-19 pandemic and its consequences have brought about a special type of business challenge. The new circumstances require an even more pronounced alignment between management and employees, their full connection and understanding of necessary changes, in order to maintain business continuity in very challenging pandemic conditions. Emergencies and numerous changes in response to a challenging situation can very often disrupt normal arrangement or functioning of business. This study focuses on the role of remote work (working from home) during the COVID-19 pandemic. The theoretical framework of this paper is based on the relationship between technology, agile organizations and working from home during the coronavirus crisis.